Electricity Capital and Energy Poverty Perspectives From Developmental States and Decentralised Markets - Baker, Lucy H.; Cao, Umberto; Chipango, Ellen Fungisai; Fathoni, Hilman Syahri; Munro, Paul G.; Samarakoon, Shanil; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
This open access book explores the rise of new forms of electricity capitalism, examining how evolving energy systems shape energy consumption and access in five different case studies from the global South. Structured in seven chapters, it begins with a clear theoretical and conceptual foundation and is followed by five compelling case studies, grounded in research insights from Zimbabwe, Mexico, Uganda, Indonesia, and Vanuatu. The book concludes with a synthesis of these findings, paving the way for future discussions on energy poverty in the context of electricity capitalism in the Global South. Lucy H. Baker is a Senior Lecturer in Environmental Geography at the Open University and a visiting Associate Professor in the Trilateral Research Chair in Transformative Innovation and Sustainable Development, University of Johannesburg, South Africa. Umberto Cao is an anthropologist, researcher at the public health dep. of Aix-Marseille University (France). His research focuses on social mobilisations for energy justice, especially among indigenous groups. Ellen Fungisai Chipango is a Senior Research Associate at the University of Johannesburg, with research interests in political ecology, feminist political ecology, energy and environmental justice, decolonial development paradigms as well as ethics and morality of energy policy Hilman Syahri Fathoni is a Herb Feith scholar and doctoral researcher at Monash University. His research interests broadly focus on rural development, socio-cultural change, community empowerment and techno-ecological transformation, taking Eastern Indonesia as his main empirical focus. Paul G. Munro is a Scientia Associate Professor in Human Geography at UNSW, Sydney. He has established research record in the fields of political ecology and environmental history, and has written extensively on forest governance and energy justice Shanil Samarakoon is a Research Associate in Human Geography at UNSW Australia. As reflected in his research record, he has a strong interest in issues of energy justice associated with energy transitions in the Global South.
Chapter 1. Electricity Capital and Energy Poverty -- Chapter 2. Energy poverty and developmental state capitalism in Indonesia: A geographical political economy reading.-Chapter 3. The paradox of energy poverty datafication in Zimbabwe: An African Ubuntu view -- Chapter 4. Uganda: The Political Economy of off-grid Solar Capitalism -- Chapter 5. Of energy transitions and the State. The case of Mexico$1 (Bs attempted electricity reform -- Chapter 6. Vanuatu and the ecologies of solar waste.-Chapter 7.Conclusion.s
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Environmental sciences -- Social aspects; Energy policy; Energy and state; Environmental geography; Science -- Social aspects; Economics; Power resources; Environmental Social Sciences; Energy Policy, Economics and Management; Integrated Geography; Science and Technology Studies; Political Economy of Energy